2019
DOI: 10.3389/fphar.2019.00568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Veratrilla baillonii Extract on Hepatic Gene Expression Profiles in Response to Aconitum brachypodum-Induced Liver Toxicity in Mice

Abstract: This manuscript was aimed to explore the hepato-protective effect of water extract of Veratrilla baillonii Franch. (Gentianaceae) (WVBF) on serious hepatic toxicity induced in mice treated with Aconitum brachypodum Diels (Ranunculaceae) at transcriptome level. The physiological and pathological symptoms were evaluated as the markers for hepato toxicity induced by A. brachypodum Diels (CFA) extracted compounds. Moreover, gene chip method was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…S20140710) were deposited at the Herbarium situated in the College of Pharmaceutical Sciences at South-Central University for Nationalities, Wuhan, Hubei, P. R. China. The WVBF was extracted as described previously (Ge et al, 2016;Yu et al, 2016;Li et al, 2019). Briefly, WVBF was prepared by extracting the plant (200 g) crushed into small pieces.…”
Section: Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…S20140710) were deposited at the Herbarium situated in the College of Pharmaceutical Sciences at South-Central University for Nationalities, Wuhan, Hubei, P. R. China. The WVBF was extracted as described previously (Ge et al, 2016;Yu et al, 2016;Li et al, 2019). Briefly, WVBF was prepared by extracting the plant (200 g) crushed into small pieces.…”
Section: Extract Preparationmentioning
confidence: 99%
“…V. baillonii, a traditional folk medicine, has been widely used in the treatment of hepatitis-induced jaundice and drug-induced hepatitis for decades (Olennikov et al, 2015;He et al, 2015). The water extract of V. baillonii (WVBF), which contain flavonoids, iridoid glycosides, and other substances (Vaidya et al, 2009;Ge et al, 2016;Yu et al, 2016;Zhang S. R. et al, 2018;Li et al, 2019). WVBF has significant protective effects on oxidative stress-induced liver injury (Dai et al, 2018), diabetic liver injury (Lian et al, 2010), and drug liver toxicity (Huang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has identified that WVBF could attenuate hepatic toxicity induced by Aconitum brachypodum Diels (Ranunculaceae) in vivo and in vitro (Ge et al, 2016;Yu et al, 2016;Dai et al, 2018b;Cheng et al, 2019;Huang et al, 2019;Li et al, 2019). Further study revealed that the anti-diabetic and hepatic protection activities of WVBF is mediated by IRS-1/PI3K/AKT signal pathway in T2DM db/db mice.…”
Section: Introductionmentioning
confidence: 96%
“…Gentiopicroside, sweroside, and swertiamarin are the characteristic components of the medicinal plants of Gentianaceae used in the practice of traditional Chinese Medicine. Our previous study identified that WVBF are rich in sweroside, swertiamarin, gentiopicroside (GP) (Ma et al, 2018), which can exert anti-hepatotoxic and hepatoprotective effects (Dai et al, 2018a;Li et al, 2019). Among many Chinese herbal extracts with hepatoprotective activity, the extracts of gentian plants endow uniquely advantages, including hepatoprotection and rescue of liver injury (Zhao et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation